Protective Role of Stem-Bark Ethanolic Extract of Sumbloo (Berberis Lycium Royale) against Rifampicin Induced Liver Damage in BALB/C Mice (Medical Forum Monthly, 2020)
Objective: To explore protective impact of stem-bark ethanolic extract of Sumbloo (Berberis Lycium Royale) against Rifampicin induced hepatotoxicity in BALB/c Mice.Study Design: Explorative randomized control studyPlace and Duration of Study: This study was conducted at Animal Chamber of National Institute of Health (NIH), Islamabad in collaboration with Islamic International Medical College (IIMC), Army Medical College (AMC) & Riphah Institute of Pharmaceutical Sciences (RIPS) from April 2014 to May 2014.Materials and Methods: This experimental study was performed on 56 male BALB/c mice. They were arbitrary split up into 4 groups (n=14). Control Group A was kept on rodent pellet diet and water only. Drug treated group Group B was loaded with Rifampin 50mg/kg BW whereas Less dose group C & High dose ethanolic extract Group D were given Rifampicin low dose (150mg/kg BW) and high dose (200mg/kg BW) of Ethanolic extract of stem bark of the Sumbloo via gavage tube respectively. Baseline blood samples collected at day 0 and normal values of serum Alanine aminotransferase (ALT) were estimated. Mid-cycle blood sampling taken at day 15 to evaluate the progress of experimental study. Final blood sampling performed on day 30 by intra-cardiac puncture. Serum was stored in sterile tubes at 4oC for analysis of serum Alanine aminotransferase(ALT). Data analysis performed on SPSS version 20 and p-value (<0.05) regarded as statistically significant.Results: Ethanolic extract of stem bark of Sumbloo depicted marked improvement of serum Alanine aminotransferase (ALT) values in group C & D. Serum ALT value of (17-77 U/L) was labeled as normal. Group A depicted normal value of (54 U/L). Group B manifested severe hepatoxicity as shown by very high value of (186.1 U/L). Serum value of ALT measured in Group C was (96.6 UL) & (56 UL) in Group D.Conclusion: Ethanolic extract of stem-bark of Sumbloo (Berberis lycium Royale) possesses remarkable protective potential for liver toxicity in high doses as compared to less dose.